Curbing Piracy in the Gulf of Guinea for Improved Maritime Security: Prospects for Nigeria - Aliyu, Rufai (NIU Journal of Social Sciences, 2021)
Since the evolution of piracy, from the Cilician, Greek, Chinese, Barbary and Caribbean pirates to Somali, Malacca Straits, South China sea and the present pirate situation in West Africa, they had operated or still operates in the absence of state authorities or sometimes in collisions with the state authority. However, in modern times, the presence of pirates could be primarily tracked to the Straits of Malacca in the South China Sea, off the coast of Somalia and in the Gulf of Guinea, the latter which forms the basis of this paper. Pirates attacks in the Gulf of Guinea is and has taken a worrisome trend, in so much that, unlike the Somali pirates, the Gulf of Guinea pirates attack cargoes especially the oil loaded ones thus, hurting maritime security in the coastal states located in the Gulf.